Lietuvos miestų istorinių priemiesčių genezės, raidos ir vertybių ypatumai (Kaunas, Klaipėda, Kėdainiai) - Dijokienė, Dalia (Journal of Architecture and Urbanism, 2006)
Peculiarities of genesis, development and values of historic suburbs in Lithuanian towns (Kaunas, Klaipėda, Kėdainiai) The object of investigation is the historic suburbs of Kaunas, Klaipėda and Kėdainiai. The investigation includes an analysis of the following urban structure elements of the suburbs: the network of streets; the structure of land holdings; the type of building–up of squares, streets and land holdings; complexes and ensembles of buildings; peculirities of natural setting; panoramas and silhouettes; compositional links with the old town’s kernel; urban and architectural pecularities of the studied historic suburbs preserved up to now. The investigation also provides the reasons of the genesis of the suburbs and a summarized description of their formation period, singles out factors that determined urban peculirities of the suburbs and sets out their types. The dispersion of the most valuable elements of the urban structure of the historic suburbs, that have preserved the highest number of authentic features, is illustrated. Article in Lithuanian. Santrauka. Nagrinėjami Kauno, Klaipėdos ir Kėdainių istoriniai priemiesčiai. Aptariami šių miestų priemiesčių urbanistinės struktūros elementai: gatvių tinklas; posesinė struktūra; aikščių, gatvių, posesijų apstatymo pobūdis; statinių kompleksai ir ansambliai; gamtinių sąlygų ypatumai; panoramos ir siluetai; kompoziciniai ryšiai su senuoju miesto branduoliu; iki šių dienų išlikę tiriamų istorinių priemiesčių urbanistiniai ir architektūriniai ypatumai. Nusakomos priemiesčių kilmės priežastys; apibendrinamas jų atsiradimo laikotarpis; išskiriami veiksniai, lėmę urbanistinius priemiesčių ypatumus; priemiesčiai tipizuojami. Iliustruojama vertingiausių, išlaikiusių daugiausia autentiškų bruožų istorinių priemiesčių urbanistinės struktūros komponentų sklaida. Reišminiai žodžiai: istorinė ir urbanistinė miesto raida, istoriniai priemiesčiai, istorinė ir kultūrinė vertė, miesto savitumas, paveldas. First Published Online: 22 May 2013